THE ROLE OF INTERNATIONAL FINANCIAL REPORTING STANDARDS ADOPTION IN THE EXTENT OF DISCLOSURE ON CORRUPTION IN AFRICA - Caleb Opoku Mensah (EPRA International Journal of Research and Development (IJRD), 2022)
The study examines the level of corruption disclosure and the adoption of IFRS in 27 African nations using unbalanced panel data from 2003 to 2020. The Arellano-Bond dynamic panel data method, generalized linear model, and linear regression were the three panel methodologies used in the study to analyses the data and draw statistically significant conclusions. According to the study, the extent of disclosure has a positive impact on corruption in Africa and the adoption of IFRS has a negative impact on it. However, the analysis using generalized linear models and linear regression showed that the dynamic panel data method had a negative impact on corruption. More studies investigating the adoption of IFRS in developing countries are advised because the study’s findings are best viewed as suggestive rather than conclusive.